Bulk Interpenetration Network of Thermoelectric Polymer in Insulating Supporting Matrix - Lu, Guanghao; Bu, Laju; Li, Sijun; Yang, Xiaoniu (Advanced materials (Weinheim), 2014)
Thermoelectric properties of conjugated polymers are found to improve upon homogeneously distributing conjugated polymer into an insulating supporting matrix. The local one‐dimensional charge transport along the interpenetration conductive network simultaneously leads to lower thermal conductivity, higher electrical conductivity without sacrifice of Seebeck coefficient, and thus a higher figure of merit ZT, as compared with neat conjugated polymer.